Genomic Characterization of Selected ESKAPEEE Clinical Isolates From Mbarara Regional Referral Hospital, Southwestern Uganda: Resistome, Multilocus Sequence Typing, Mobilome, and Virulome - Judith Owokuhaisa; Joel Bazira; Moses Mpeirwe; Godwin Tusabe; Edgar Mulogo (Cureus, 2026)
Background: The global dissemination of Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococcus faecium, Enterococcus faecalis, and Enterobacter cloacae pathogens is increasingly driven by the convergence of multidrug resistance (MDR) and hypervirulence. These opportunistic pathogens are characterized by their ability to "escape" the bactericidal effects of conventional antibiotics through a refined repertoire of resistance mechanisms. Infections related to these pathogens are responsible for the majority of hospital-acquired infections (HAIs) globally, leading to increased morbidity, mortality, and healthcare costs. Methods: This study used whole-genome sequencing to identify the resistome, virulome, mobilome, and multilocus sequence types of selected clinical Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococcus faecalis, and Enterobacter cloacae pathogens. Results: Molecular profiling revealed a diverse virulome, with Pseudomonas aeruginosa (ST244) exhibiting the most expansive repertoire (>130 virulence factors (VFs)), including type III secretion system effectors (exoS, exoT) and complete alginate biosynthesis (alg) clusters. S. aureus (ST1) demonstrated a potent toxigenic profile characterized by the Panton-Valentine Leukocidin (lukF/S-PV) and toxic shock syndrome toxin-1 (tsst-1) genes. Among the Enterobacteriaceae, virulence was dominated by the yersiniabactin ( ybt) and enterobactin (ent/fep) iron-acquisition systems, which were notably conserved across Klebsiella pneumoniae (ST307) and E. coli (ST448). Furthermore, the presence of the Escherichia coli common pilus (ecp) and curli fimbriae (csg) across multiple species suggests that mobile genetic elements (MGEs) facilitate the horizontal transfer of "survival packages" that combine colonization and persistence traits. In addition, these isolates also revealed diverse plasmids varying significantly in size (1,570 bp to 235,562 bp) and GC content (0.28 to 0.65). Conjugative plasmids were exclusively large (>60 kb) and characterized by the presence of both a relaxase (primarily MOBH or MOBP) and a mate-pair formation (MPF) system (predominantly MPF_F and MPF_T). Conclusion: These findings identify a critical genetic variation where high-risk bacteria combine multidrug resistance with an enhanced ability to cause disease. The emergence of these multidrug-resistant bacteria highlights an urgent need for genomic tracking in clinical settings to monitor and prevent their spread.
Keywords: eskapee pathogens; high-risk clones; mobile genetic elements (mges); multi locus sequencing; resistome; virulome